Os papéis do psicológico na filosofia de Wittgenstein: do tractatus às investigações - Magalhães, Tiago de Oliveira (2010)
The present study intends to enlighten the role that the reflection on psychological issues performs in Wittgenstein’s philosophy, embracing the most remarkable moments of the period that goes from his first philosophical book until his main mature work. In order to do it, the capital features of his thought are presented, so that it becomes possible to identify the function displayed by his awareness on that subject field. Thus, the development of the wittgensteinian philosophy itself is a highlighted topic. What can be noticed throughout this process is the philosopher permanent and explicit concern in making clear the structural distinction between the philosophical task and any form of scientific research on mental world, going along with a progressive enhancement of his interest on the psychological as matter of the philosophical activity. The conclusion is that both aspects are fundamental traits of Wittgentein’s thought.